2014
DOI: 10.1111/are.12536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ploidy on the mortality ofCrassostrea gigasspat caused by OsHV-1 in France using unselected and selected OsHV-1 resistant oysters

Abstract: The effect of ploidy on the mortality of Crassostrea gigas spat caused by the ostreid herpesvirus (OsHV‐1) genotype μVar was investigated at five sites along the Atlantic coast in France in 2011. Sibling diploids and triploids were produced using either unselected or selected OsHV‐1‐resistant oysters. No significant interactions were found between the factors of environment, genotype and ploidy at the endpoint dates. The mean mortality rates at the sites were 62% and 59% for diploids and triploids, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Triploid oysters now represent a significant portion of the oyster production worldwide. It was recently reported that mortality related to OsHV-1 is not affected by ploidy level (Dégremont et al, 2014b), which agrees well with studies conducted on other bivalve species and their pathogens (Smith et al, 2000;Nell, 2002…”
Section: Genetic Background and Ploidy Of Oystersupporting
confidence: 90%
“…Triploid oysters now represent a significant portion of the oyster production worldwide. It was recently reported that mortality related to OsHV-1 is not affected by ploidy level (Dégremont et al, 2014b), which agrees well with studies conducted on other bivalve species and their pathogens (Smith et al, 2000;Nell, 2002…”
Section: Genetic Background and Ploidy Of Oystersupporting
confidence: 90%
“…Because of the fast growth, superior meat quality and the ease to produce, “natural” triploids have been commercially produced worldwide. Currently, triploid Pacific oysters account for about 50% of the production in the US northwest coast, and most hatchery produced seed in France (Degremont, Ledu, Maurouard, Nourry & Benabdelmouna, ); triploid eastern oysters account for nearly 100% in Chesapeake Bay in the United States, and that of the Pacific oyster and Sydney rock oyster accounts for about 15% of the production in Australia (Peachey & Allen, ). Triploid production has become an important part of the oyster culture industry worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that either tetraploid lines need to be produced from selected diploid broodstocks or hatcheries need to be provided with the best breeders that have the greatest resistance to OsHV‐1 (Dégremont et al . ).…”
Section: Animal Host Factorsmentioning
confidence: 97%
“…Dégremont et al . () found that both diploid and chemically induced triploid C. gigas had similar mortality that could be high using unselected parents or low using parents selected for their higher resistance to OsHV‐1. In Ireland, diploid C. gigas had a greater mortality risk (e.g.…”
Section: Animal Host Factorsmentioning
confidence: 99%
See 1 more Smart Citation